Pengaruh Pertumbuhan Ekonomi dan Kesempatan Kerja terhadap Indeks Pembangunan Manusia di Kabupaten Banjar - Jannaty, Nabielah Farrasy (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
Carried out during the construction of the government sometimes does notcorrespond to the actual needs of the community. The pattern of government that is notbased on the needs of the city may be lead to cuts in public welfare in the area, as seenfrom high to low Human Development Index (HDI) as a benchmark. Human developmentis a process of growth that aims to have more choices, particularly in income, health, andeducation.This research is a quantitative study using secondary data, the data used in thetime series in 2006-20016—analysis of data using a linear regression method. Thepurpose of this study is to analyze how much influence the variables of economic growthand employment simultaneously and partly variable HDI and determine which variablemost dominant influence variable.The results showed the simultaneous effect of two independent variablesdetermination coefficient of 0,696 (R-square). And when tested, partially showingeconomic growth and no significant positive impact on the HDI. Employment andsignificant positive effect on the HDI and the most dominant variable that has seen thework of t-count and most sig-t close to 0 (zero).